2 - Essential Medicines in Nigeria: Foregrounding Access to Affordable Essential Medicines - Chinwe Obuaku, (African Sociological Review, 2016)
Within every functional healthcare system, access to quality and affordable essential medicine stands out as one of the building blocks. However, its significance has been underrated due to poor advocacy and research. The implication is that access to quality and affordable essential medicines remains a challenge to many people in low / middle income countries and could create difficulty in the attempt to reform healthcare systems and save lives if not given ample attention. This paper presents a critical discussion of the Nigerian health system with special focus on access to essential medicines as a component of the Nigerian healthcare system by drawing upon primary data, using qualitative research method.